Vão-se os anéis, ficam os dedos: reconfiguração da elite empresarial brasileira pós financeirização econômica - Julian, Erica Ambiel (2018)
In Brazil, the elite helped building policies. In order to get benefits for different sectors, the agents seek ways to get some power spaces, integrating influence spaces or occupying some strategic positions and chairs, such as councils, elected offices and class representation. This construction of specific policies for certain sectors is done with the direct or indirect help from the opinion of their most outstanding representatives. Understanding how elite influence the government actions is important to project the influence of the elite in the state political formation. In relation to the economic elite, it is possible to verify this assertion by observing the relation between the business people and the political groups. The entrepreneurs become relevant agents upon the national political thought, boosting the country’s directions, advising the governments that focus on development, creating discourses on behalf of economic interests. By analysing how they act in the political scenario, it is possible to perceive that the action is adapted to the context, distinguishing the ways of operating the relations between political and economic spaces according to the temporary cut. Therefore, it is possible to see that, almost in an instinctive form, the economic elite, or business people, use different entries to the political environment to defend their interests. In this work, we will explore how the economic elite have access to the political elite or to the entries to the political field. Gerdau is a one-hundred-year familiar company that, after the financialization of its operations and a bigger internationalization, has suffered organizational changes that have resulted in a significantly changing in its management staff. Gerdau has one of the most recognized representatives of the corporate class in the country, Jorge Gerdau Johannpeter, who takes part in the organization evolution and has already been director and president and, currently, is an advisor to the Group. In observing his biography, it is possible to understand that the agent's form of action, coming from the economic elite that transfers capital to the political field, is modified according to the institutional changes that politics imposes on the nation state. This conclusion was obtained after the data collection, found through the media collection made available by the Brazilian Digital Library (Hemeroteca Digital Brasileira da FundaçãoBiblioteca Nacional) and other sources.